Enteral nutrition in 6 Malaysian intensive care units: a point prevalence study of prescription practices - Azahar, Aizad; Ibrahim, Noor Airini; Lim, Thiam Aun (International Islamic University Malaysia, 2020)
Introduction: Enteral nutrition (EN) is the first line of nutrition therapy for critically ill patients with an intact gastrointestinal tract. Even though intensive care units (ICUs) generally have established feeding protocols, prescribing practices to achieve nutrition goal is still widely variable among intensive care practitioners. The aim of this study was mainly to investigate commonly prescribed types and energy concentration in EN formulations including protein prescription. Materials and methods: This was an observational, point prevalence study, involving six level 3 ICUs in Malaysia. All patients aged type of EN formulation and protein prescription recorded. RESULTS: A total of 109 patients were included in the analysis out of which 78% of them were mechanically ventilated. At the point of the study, more than 16 years of age in the participating ICUs on the 11th of October 2016 were enrolled in this study and 71.5% (78/109) received EN. Among the EN group, 68% (53/78) received standard formulation feeds (1kcal/ml) while the rest received energy dense formulation (>1kcal/ml). Fluid restriction was the main indication for energy dense formulation prescription, occurring in almost all (24/25) of the patients. There was no report of feeding intolerance. Only 2/109 received parenteral nutrition (PN) giving the EN to PN ratio of 30:1. The mean protein prescription was 0.9g/kg (SD± 0.4). Conclusion: Prescription of EN was 30 times more frequent than PN in these ICUs. In those receiving EN, standard formulation feed was 3 times more commonly prescribed than energy dense feeds with fluid restriction being the main indication of the latter. Protein prescription was less than the guideline recommendation.